Production of nutraceutical chocolate brownies by incorporation of Magnifera Indica leaves extract - Raza, Rashid; Yousuf, Sania; Khalid, Misbah; Naveed, Minal; Ghaznavi, Muqita; Temuri, Wajiha (Journal of Research (Science), 2025)
Product development is a key to success for any food industry; hence a lot of new products are launched in the market on regular intervals. Chocolate brownies were prepared by the incorporation of 5%, 10%, 15% and 20% aqueous extract of Magnifera Indica leaves with partial substitution (50%) of wheat flour by gram flour. The finished products were evaluated for shelf life, antioxidant, organoleptic and physico-chemical characteristics. The brownie sample with 10% aqueous extract of M. Indica leaves was found to be acceptable according to the sensory panel. Both of the control and samples with M. Indica have shown better organoleptic scores, making them acceptable. The moisture(%), ash(%), fat(%), titrable acidity(%), proteins(%), carbohydrates(%), fiber(%) and antioxidant activity as DPPH inhibition (IC50 ppm) was found to be 5.6 ± 0.1, 1.44 ± 0.01, 37.8 ± 0.05, 2.2 ± 0.001, 12.4 ± 0.04, 15.65 ± 0.04, 11.2 ± 0.1 and 92.23 ± 0.9 respectively. The calorific values indicate that the brownie sample with M. Indica contains only 7.6% of the total daily calorie requirements of an adult, and may not cause weight gain. The shelf life, investigated at ambient (27oC) and refrigerated (5oC) temperatures, of control sample was found to be 6 and 15 days and for the samples with M. Indica was 8 and 25 days respectively. The constituents of the product produced in the current study are natural, no artificial colour and flavour was added to prepare the brownies. The research concludes that M. Indica extract and gram flour impart the antioxidant, anticancer, anti-inflammatory, anti-diabetic and other medicinal properties in the chocolate brownie. It also has the market competent price therefore the product is likely to gain the attraction of consumer and improves the market trends.